Hazard Evaluation of Mature Urban Street Trees in Kuala Lumpur - Abd. Ghani, Murad (2000)
The hazard status of mature urban street trees in Kuala Lumpur has not being studied. Therefore, there has been a paucity of data pertaining to the current status of mature urban street trees in Malaysia. In order for municipalities to manage urban street trees effectively, a thorough understanding of the resource base is needed. Inventories and inspection are essential in order to provide a current record of resources as well as to assist in management decision making. The data obtained can be used to serve as source of information for developing tree maintenance and management programme, particularly hazard prevention programme. Thus, the purpose of this study were : (l) to determine and evaluate hazard status of mature urban street trees in Kuala Lumpur. which is limited to the central area of Kuala Lumpur. and (2) to propose guideline for a proper tree work in Malaysia. The study employed a combination of cluster and systematic sampling technique. Ten percent (232 trees) of the total street trees in the study area were sampled. The results indicated that the status of urhan street trees in Kuala Lumpur were in moderate l62.50%) to high (32.75%) hazard risk status. Only less than five percent (4.74%) had a low hazard risk status suggesting that most of the trees in the study area suffered from various structural defects requiring urgent attention by the management. Sound arboricultural practices as well as the use of systematic hazard inspection programme should be adopted in managing urban street trees in Malaysia.